2020
DOI: 10.14411/fp.2020.021
|View full text |Cite
|
Sign up to set email alerts
|

The Proteocephalus species-aggregate (Cestoda) in sticklebacks (Gasterosteidae) of the Nearctic Region, including description of a new species from brook stickleback, Culaea inconstans

Abstract: A survey of the species of the Proteocephalus-aggregate from sticklebacks (Actinopterygii: Gasterosteidae) is provided. The occurrence of three species in North America is confirmed: (i) Proteocephalus filicollis (Rudolphi, 1802), which has been reported from the three-spined stickleback, Gasterosteus aculeatus Linnaeus, in the northeastern part of North America (Newfoundland); (ii) Proteocephalus pugetensis Hoff et Hoff, 1929 occurs also in G. aculeatus, but in northwestern North America (British Columbia and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…FM956086, FM956087). Scholz et al, 2020a , Scholz et al, 2020b provided molecular evidence these tapeworms belonged to M. giganteum , a typical parasite of the channel catfish, Ictalurus punctatus (Rafinesque). Bowfin is considered as an accidental host of M. giganteum .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…FM956086, FM956087). Scholz et al, 2020a , Scholz et al, 2020b provided molecular evidence these tapeworms belonged to M. giganteum , a typical parasite of the channel catfish, Ictalurus punctatus (Rafinesque). Bowfin is considered as an accidental host of M. giganteum .…”
Section: Resultsmentioning
confidence: 99%
“…This species aggregate was proposed by de Chambrier et al (2004) to accommodate closely related and morphologically similar Nearctic and Palaearctic species of the monophyletic clade that contains the type-species of the genus, Proteocephalus ambiguus (Dujardin, 1845) ( Scholz et al, 2007 ). Recent taxonomic revisions based on morphological and molecular evaluation of museum and newly collected material of fish tapeworms have shown that the actual number of valid species of this aggregate is considerably lower and only 15 species are currently recognised as valid in North America ( Scholz et al, 2019 ; 2020a , 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Tapeworms of the genus Proteocephalus are parasites reported in fish, amphibians and reptiles [ 33 ]. Among the fish species, authors reported the presence of parasites belonging to the genus Proteocephalus from brook stickleback, Culaea inconstans (Kirtland, 1840), sampled in the Neartic Region [ 29 ], Perca fluviatilis (Linneus 1758) [ 34 ] and in coregonid and salmonid fish from North America [ 35 ]. In accordance with these data, our study reports the occurrence of Proteocephalus sp.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, scolex, intermediate and terminal parasite sections were stained in acetocarmine red solution for 12 h, bleached in chloride acid–alcohol solution (1%), washed three times in distilled water to remove any excess of hydrochloric acid, dehydrated in increasing alcoholic solutions for 5 min each (70°, 80°, 90°, 95°, 100°), clarified in clove essential oil (BioSigma, Venice, Italy) for 1 h, and then mounted with Canada balsam. Parasite morphological identification was carried out under an optic microscope (Axioskop 2 plus Zeiss, Jena, Germany) following the keys suggested by Alexander [ 27 ], de Chambrier [ 19 ] and Scholz [ 28 , 29 ]. All images were acquired with the aid of a digital camera (Axiocam Mrc Zeiss, Jena, Germany) supported by a digital image acquisition system (Axiovision Zeiss, Jena, Germany).…”
Section: Methodsmentioning
confidence: 99%